The impact of kinesio taping on pain relief in patients with lateral epicondylitis - Breda Jesenšek Papež (Acta Medico-Biotechnica, 2021)
Purpose: To compare the short–term effect of kinesio taping on reducing pain in subjects with lateral epicondylitis (LE) treated with physiotherapy alone compared to physiotherapy withkinesio taping.Methods: We retrospectively reviewed the medical documentation of 188 patients diagnosed with LE and treated between January 2012 and December 2013. Ninety–five patients who were treated with the same multi–modality physiotherapy with or without kinesio taping (T0 and T1 groups, respectively) were included in our analysis. Pain intensity was measured using a visual analogue scale (VAS) before therapy and after therapy was concluded. To compare the groups, we used Student's t–test and Pearsons χ2–test. To compare the VAS score of the two groups before and after treatment, we used analysis of variance for repeated measurements. Statistical significance was set at p<0.05.Results: The mean VAS score prior to treatment (VAS1) in theT0 group was 6.3±1.5 (range, 4–9; median, 6), andthe mean VAS score in the T1 group was 6.4±1.8 (range, 3–10; median, 6.5). The mean VAS score after treatment (VAS2) in theT0 group was 2.1±1.7 (range, 0–7; median, 2), and the mean VAS score in the T1 group was 1.4±1.6 (range, 0–6; median, 1). The pain in both groups was significantly reduced (p<0.001), whereas the difference between the two groups was not statistically significant at the 0.05 level, although marginally (p=0.056).Conclusions: Based on a retrospective analysis, we were not able to confirm the short–term effect of kinesio taping on reducing pain in subjects with LE; however, due to the low probability of obtaining our results by chance (< 6%), it is reasonable to suggest that the use of KT may be effective in treating LE.